Respostas

2014-02-25T13:25:19-03:00
RESOLUÇÃO...

De acordo com as propriedades de potenciação  a^{-1} =  \frac{1}{a}  

[*NOTA:  a é um número genérico.]



 1ª) Nos é dado que:                    (x^{-1} +  y^{-1} ) ^{-1} = 2

                                                  (\frac{1}{x} +  \frac{1}{y}) ^{-1}= 2
           
                                                ( \frac{y+x}{xy}) ^{-1} = 2
          
                                                 \frac{xy}{y+x} = 2
 
                                                2y + 2x = xy
            
                                                xy = 2y + 2x

                                                xy - 2y = 2x

                                                y(x-2) = 2x

                                                y =  \frac{2x}{x-2}
           

11 4 11